2020
DOI: 10.1007/s10549-020-05929-3
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT in high-risk primary breast cancer—a prospective study of stage migration and clinical impact

Abstract: Purpose To investigate the clinical impact of FDG-PET/CT for staging and treatment planning in high-risk primary breast cancer.Methods Women with high-risk primary breast cancer were enrolled between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 18 publications
3
54
1
Order By: Relevance
“…In nine patients, the origin of the detected metastases was suggested to be breast cancer, and [ 18 F]FDG-PET/CT suggested synchronous cancer in the remaining 9 of 225 patients (4%). This number corresponds well with the 3.88% of incidental ndings in a population of high-risk primary breast cancer in the same institution and time [10]. Other studies on different cancers have also found between 1-8% of additional malignancies at [ 18 F]FDG-PET/CT [9,[15][16][17][18].…”
Section: Accuracysupporting
confidence: 79%
See 2 more Smart Citations
“…In nine patients, the origin of the detected metastases was suggested to be breast cancer, and [ 18 F]FDG-PET/CT suggested synchronous cancer in the remaining 9 of 225 patients (4%). This number corresponds well with the 3.88% of incidental ndings in a population of high-risk primary breast cancer in the same institution and time [10]. Other studies on different cancers have also found between 1-8% of additional malignancies at [ 18 F]FDG-PET/CT [9,[15][16][17][18].…”
Section: Accuracysupporting
confidence: 79%
“…The study was registered at ClinicalTrials.gov with an enrolment of patients with high-risk primary breast cancer. This population has been described elsewhere as the clinical impact of [ 18 F]FDG-PET/CT differs between patients with high-risk primary breast cancer and patients suspected of recurrent breast cancer [10]. Another strength is that we managed to reproduce and validate the diagnostic accuracy of an earlier study [4].…”
Section: Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…In another recent study, of 103 women, 24 (23%) were diagnosed with distant metastases by FDG-PET/CT [60]. Based on these findings, breast surgery was omitted in 18.…”
Section: Contribution Of Pet/ct In the Assessment Of Extension Of Breast Cancermentioning
confidence: 99%
“…Twentynine incidental findings were detected in 24 women (23%), leading to further examinations in 22 and diagnosis of eight (8/22, 36%) synchronous diseases: cancer (n = 4), thyroiditis (n = 2), aorta aneurysm (n = 1), and meningioma (n = 1). The authors concluded that FDG-PET/CT should be considered for primary staging in high-risk primary breast cancer to improve treatment planning [60].…”
Section: Contribution Of Pet/ct In the Assessment Of Extension Of Breast Cancermentioning
confidence: 99%